Pectic Oligosaccharide from tomato exhibiting anticancer potential on a gastric cancer cell line: Structure-function relationship. (15th March 2017) - Kapoor, Sabeeta; Dharmesh, Shylaja M.
Highlights: Sour raw tomato oligosaccharide SrTPO has inhibited the gastric cancer in in vitro. We investigated that SrTPO1 fraction is mainly responsible for the activity of SrTPO. Structural features of SrTPO plays an important role as therapeutics against cancer. SrTPO rich in galactose along with rhamnose were responsible for its effects. Abstract: Pectic Polysaccharide (PP) from dietary sources has been known to prevent cancer growth and hence impede cancer progression. We evaluated anticancer effect of Pectic-Oligosaccharide isolated from Sour Raw Tomato (SrTPO); its bioavailability and structure elucidated from purified fraction (SrTPO1). SrTPO1 inhibited galectin-3 activity with MIC of 0.25 ug/mL (100 fold better than standard galactose), inhibited the growth of AGS cells (IC50 3.4 μg/mL) and induced apoptosis (70% inhibition at 30 μg/mL concentration). Normal– NIH 3T3 cells were not affected by SrTPO as opposed to doxorubicin, a known anticancer drug, which reduced 76% viability at equivalent dose. SrTPO1 was identified as RhamnogalacturonanI-arabinogalactan (RGI-AG), where repeated alternative rhamnose and galacturonic acid residues were observed while arabinose in the branch point and β-1, 4 linked galactose in the linear chain form. SrTPO was found to be bioavailable as evaluated by FITC labelled oligos inside the cell, which was in reciprocal proportion with apoptosis.